A short tour by the history of The Partido del Trabajo de España (PTE) - Díaz Macías, Ernesto M. (Hispania Nova, 2021)
The revolutionay left´s history of the Spanish Transition has been marginalised by the oficial history. The Partido del Trabajo de España (PTE) was the biggest comunist organization, but his history is unknown. This article tries to recover some notes related to its history.
Keywords: transition; political party; comunism; democratic breakdown; democratic opposition